Kajian Potensi Sungai Srinjing Untuk Pembangkit Listrik Tenaga Mikrohidro (Pltmh) Brumbung Di Kabupaten Kediri - Indarto, Agus; Juwono, Pitojo Tri; Rispiningtati, Rispiningtati (Fakultas Teknik, Universitas Brawijaya, 2012)
MHP Brumbung is located at upstream of Srinjing River. Potential discharge MHP Brumbung depends on the discharge of the gate 1 operation of Siman dam which is used to irrigate 4852 Ha Siman crop area.To obtain the optimal scale in the construction of the MHP to be optimized flow generation and generating units in order to obtain an economical MHP. Dependable discharge optimization results are used as a basic for discharge planning of Brumbung MHP is discharge with 75% probability that is equal to 3.394 m3/dt with the discharge for one unitinstalled capacity is equal to 1.697 m3/dt and installed capacity of 50 kW,with fluctuating effective head ranged from 4.944 m to 5.140 m, the annual energy production obtained 875,785.980 kWH for two generating units with a turbines Crossflow.Keywords: Micro hydropower, discharge optimization, installed capacity